To See Invisible Rights: Quantifying Araman informal tenure and its immediate relationship with Social Forestry in Central Java, Indonesia - Cummins, Alex; Yamaji, Eiji (Forest and Society, 2019)
The process of formalizing traditional, unwritten tenure systems is no simple task. Inaccurate or incomplete representation of the informal system may create more problems for the local communities. As such, a full understanding of the local informal tenure systems is necessary before implementing any type of land reform. This paper discusses a case study conducted in the Tawanmangu area of Central Java, Indonesia, in which the informal system known as Araman is quantified on paper with the help of the Tenure Map tool, survey, and interview. The challenges of quantifying and understanding an informal system are discussed with the following viewpoints: key aspects of the Araman structure, the relationship between the informal Araman system and the formal Social Forestry system also present in the area, and finally comments on the strengths and weaknesses of the Tenure Map tool after using it in the field.